Probabilistic study of bone remodeling using finite element analysis - Werner, C.; Gorla, Rama Subba Reddy (Zielona Góra: Uniwersytet Zielonogórski)
The dynamic bone remodeling process is a computationally challenging research area that struggles to understand the actual mechanisms. It has been observed that a mechanical stimulus in the bone greatly affects the remodeling process. A 3D finite element model of a femur is created and a probabilistic analysis is performed on the model. The probabilistic analysis measures the sensitivities of various parameters related to the material properties, geometric properties, and the three load cases defined as Single Leg Stance, Abduction, and Adduction.
Keywords: probabilistic analysis; bone remodeling; finite element analysis